Analisis Pajak Penghasilan Orang Pribadi di Era Digitalisasi di Indonesia - Nor Hasan; Sulistyorini Sulistyorini; Septia Nur Rahmawati; Nur Afni Latansya; Putri Febby Firnanda (MANAJEMEN, 2026)
This study aims to analyze the development of Individual Income Tax in the digitalization era in Indonesia and to determine the effect of tax digitalization on individual taxpayer compliance. This study uses a qualitative method with a descriptive approach through the use of secondary data obtained from the annual reports of the Directorate General of Taxes for 2021–2024, the 2025 Annual Tax Return submission press release, scientific journals, articles, and other official sources related to taxation and tax digitalization in Indonesia. Data collection techniques were carried out through literature studies and documentation, while the data analysis technique used descriptive qualitative analysis. The results of the study indicate that tax digitalization in Indonesia has developed significantly through various innovations in tax administration systems such as e-filing, e-billing, NIK-NPWP integration, and the development of the Core Tax Administration System. Tax digitalization has a positive impact on individual taxpayers because it facilitates the process of reporting and paying taxes more quickly, practically, and efficiently. In addition, digitalization also helps the government improve the effectiveness of supervision and tax data management. However, the implementation of tax digitalization still faces several challenges, such as low tax literacy and digital literacy in society, as well as the complexity of supervising digital economic activities. Therefore, it is necessary to improve tax education, strengthen digital supervision systems, and improve the quality of technology-based tax services so that individual taxpayer compliance can increase optimally.